Implementation of the Trilingual Handbook and Anti-Bullying Action for Teacher Working Group in Enrekang City - Jabri, Umiyati; Samad , Ita Sarmita; Endarwaty, Asrina (eScience Humanity Journal, 2024)
This study aimed to implement the Trilingual Handbook for English language teaching and the Anti-Bullying Action strategies across 8 elementary schools in Cluster 1, Enrekang Regency. The program was designed to improve English teaching through the integration of local wisdom-based materials and to foster safer school environments through structured anti-bullying campaigns. The Trilingual Handbook was successfully adopted by 4 out of 8 schools, demonstrating its potential to enhance language learning when effectively applied. However, challenges such as time constraints and unfamiliarity with the new methods hindered full adoption in the remaining schools. The Anti-Bullying Action strategies were implemented in 7 out of 8 schools, leading to a significant reduction in bullying incidents and improved student awareness. These results indicate that the program had a positive impact, although ongoing mentoring and support are essential to ensure full and sustained implementation across all schools.